The effect of grapeseed oil on performance, rumen fermentation, antioxidant status and subcutaneous adipose fatty acid profile in lambs. Issue 1 (26th April 2017) - Sharifi, M.; Bashtani, M.; Naserian, A. A.; Farhangfar, H.; Emami, A.
Summary: This experiment was carried out to examine the effect of grapeseed oil (GSO) on performance, rumen fermentation, antioxidant status and subcutaneous adipose fatty acid (FA) profile in lambs. Eighteen Baluchi lambs, 196 ± 14 days of age and 39.8 ± 1.7 kg body weight, were randomly assigned to three experimental diets: (i) diet without GSO (control), (ii) diet containing 2% of GSO (GSO2) and (iii) diet containing 4% of GSO (GSO4) for 42 days. Results showed that the experimental diets had no significant effect on dry matter intake and performance (p > 0.05). The supplemented diets with GSO had no effect on pH and NH 3 ‐N of rumen fluid (p > 0.05), but GSO4 increased (p = 0.003) the concentration of propionic acid and reduced (p = 0.002) the concentration of acetate acid compared to the control. Inclusion 4% of GSO to the diet increased total antioxidant activity and decreased malondialdehyde in serum and muscle (p < 0.001). The level of blood glutathione peroxidase in diets containing GSO was higher than control diet (p = 0.02), but diets had no effect on superoxide dismutase in blood and muscle tissues (p > 0.05). The concentration of vaccenic acid, rumenic acid and linoleic acid and thus polyunsaturated fatty acid in subcutaneous fat was affected by experimental diets (p < 0.001), as control had the lowest amount of these FAs and GSO4 had the highest amount of them. Therefore, it can be concluded that the use of GSO up to 4% improves the antioxidant status and adipose fatty acid profile in lambs without effects on performance.